New trends in androgen deprivation therapy: Summary of key research presented at AUA 2014 - Editorial, CUAJ (Canadian Urological Association Journal, 2014)
At the 2014 Annual Meeting of the American Urological Association (AUA), there were a number of educational sessions presenting new research regarding the use of androgen deprivation therapy (ADT). Two important themes related to ADT that emerged during the conference were the relationship between ADT and cardiovascular (CV) risk and the optimization of testosterone suppression. The following sections will provide highlights of from the AUA sessions on these two topics.